The Influence of Adult Attachment on Mental Health among Medical Undergraduates - HOU, Yongmei (Advances in Social Sciences Research Journal, 2022)
Objective To explore the present status of adult attachment and mental health, and analyze the impact of adult attachment on mental health among medical undergraduates. Methods Stratified random sampling was used to select 855 medical undergraduates from Guangdong Province, China. They were investigated with Experiences in Close Relationships Inventory (ECR) and Symptom Check-List 90 (SCL-90). Results ⑴ The scores in the both dimensions of ECR, as well as the total score of SCL-90 were (3.89±0.74), (3.77±0.55) and (1.87±0.47), respectively. The scores of obsessive-compulsive and interpersonal sensitivity were above 2.0, the lower score limit of postive symptom. (2) Multiple linear stepwise regression showed that both attachment anxiety and attachment avoidance positively predicted the total score of SCL-90 (β=.302, .280, all P<.001). Conclusion The adult attachment and mental health of medical undergraduates need to be improved. Adult attachment may be an important influencing factor of mental health.